Polycomb Repressive Complex 2 Is a Barrier to KRAS-Driven Inflammation and Epithelial-Mesenchymal Transition in Non-Small-Cell Lung Cancer - Serresi, Michela; Gargiulo, Gaetano; Proost, Natalie; Siteur, Bjorn; Cesaroni, Matteo; Koppens, Martijn; Xie, Huafeng; Sutherland, Kate D; Hulsman, Danielle; Citterio, Elisabetta; Orkin, Stuart; Berns, Anton; et al. (Cancer cell, 2016)
Polycomb repressive complexes (PRC) are frequently implicated in human cancer, acting either as oncogenes or tumor suppressors. Here, we show that PRC2 is a critical regulator of KRAS-driven non-small cell lung cancer progression. Modulation of PRC2 by either Ezh2 overexpression or Eed deletion enhances KRAS-driven adenomagenesis and inflammation, respectively. Eed-loss-driven inflammation leads to massive macrophage recruitment and marked decline in tissue function. Additional Trp53 inactivation activates a cell-autonomous epithelial-to-mesenchymal transition program leading to an invasive mucinous adenocarcinoma. A switch between methylated/acetylated chromatin underlies the tumor phenotypic evolution, prominently involving genes controlled by Hippo/Wnt signaling. Our observations in the mouse models were conserved in human cells. Importantly, PRC2 inactivation results in context-dependent phenotypic alterations, with implications for its therapeutic application.